2010
DOI: 10.20882/adicciones.215
|View full text |Cite
|
Sign up to set email alerts
|

Abandono del tratamiento en adictos a la cocaína

Abstract: The high rate of dropout from treatment programs is one of the most serious problems in the field of drug dependence. Early identification of predictors of dropout risk can provide useful information on the specific treatment needs of these types of patient. The aim of this study was to identify predictors of premature cessation of an outpatient treatment program for cocaine addicts. The study was carried out at public healthcare units in a Spanish city. Participants were 91 cocaine addicts admitted for treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
6
0
6
Order By: Relevance
“…The sample has a demographic distribution similar to that previously described in studies performed in Lima (1) and studies in other countries, where the predominance of the male gender is similarly observed. (13)(14)(15) The average age was 31 years, which corresponds to young patients, mostly under 34 years of age, similarly to that found in other studies with national samples. (11,(16)(17) This is also comparable to the age observed in other populations such as the North American and European populations, which is around 30 years.…”
Section: Discussionsupporting
confidence: 77%
“…The sample has a demographic distribution similar to that previously described in studies performed in Lima (1) and studies in other countries, where the predominance of the male gender is similarly observed. (13)(14)(15) The average age was 31 years, which corresponds to young patients, mostly under 34 years of age, similarly to that found in other studies with national samples. (11,(16)(17) This is also comparable to the age observed in other populations such as the North American and European populations, which is around 30 years.…”
Section: Discussionsupporting
confidence: 77%
“…(20)(21)(22)(23) It is known, however, that one of the best predictors of success is the completion of an entire treatment program. Various studies have suggested that patients who abandon treatment prematurely (regardless of the treatment period in question) present with, among other factors, more anxiety problems, (24) more severe addictions, (6,25) greater cognitive deficits, (26,27) more personality disorders, (25.28) greater psychopathological problems, (29) less social or familial support, or different combinations of these factors. (4,30) The combination of withdrawal from a previous treatment program and the presence of a more severe addiction profile requires that the protocols that are used in the treatment of a readmitted patient have specific adaptations that are designed to make therapeutic interventions more efficient.…”
Section: Departamento De Psicología Y Pedagogía Universidad Pública mentioning
confidence: 99%
“…Los resultados también coinciden con los estudios de pacientes que realizaban seguimiento ambulatorio. En dependientes de cocaína que seguían tratamiento ambulatorio, el 50,5% había recaído a los 6 meses (Sánchez-Hervás et al, 2010). Goeb y cols.…”
Section: Discussionunclassified
“…El resultado del presente trabajo es coherente con que la adicción a heroína se ha considerado de mayor gravedad, debido a la problemática social, familiar y a las enfermedades médicas (sobre todo infecciosas) y psiquiátricas a las que se asocia (Maremmani et al, 2011;Sánchez-Hervás et al, 2010). Maremmani y cols.…”
Section: Discussionunclassified